Studying the process of becoming a teacher educator in technology enhanced mathematics - Giorgos Psycharis; Elissavet Kalogeria (Journal of Mathematics Teacher Education, 2018)
In this paper, we explore the process of becoming a teacher educator in the pedagogical use of digital tools in mathematics teaching. The study took place in the context of an in-service program during the trainees’ engagement in their practicum fieldwork activities including the process observation–reflection–design–implementation–reflection. We explored the features of this context that facilitated the trainees’ transition from the level of trainee educator to the level of teacher educator as well as the nature of the trainees’ documentation work for teachers. The results showed that observation of other teacher educators’ teaching in conjunction with reflection during the program’s respective sessions facilitated the trainees’ transition to the professional level. The identified operational invariants underlying the trainees’ designs concerned the focus of their observation in teacher education classrooms, the importance they attributed to the constraints and opportunities provided by the wider educational context and epistemological issues regarding the teaching and learning of mathematics with technology. The analysis of trainees’ designs revealed three kinds of documents (‘‘explanatory,’’ ‘‘instructive’’ and ‘‘facilitative’’) and corresponding roles of trainees during the implementation. These documents targeted different aspects of TPACK depending on the trainees’ conceptualizations of teachers’ roles either ‘‘as students’’ or ‘‘of students.’’